An Examination of the Evolutionary Trajectories and Strategic Transformations in Film and Television Promotion Methods - Li, Zonghan (Transactions on Economics, Business and Management Research, 2024)
This scholarly investigation systematically examines the evolution of film and television promotion methods and strategies, aiming to compile and analyze the historical and contemporary approaches within the cinematic industry. The study elucidates the developmental pathways from traditional media reliance to the current digital-centric strategies, emphasizing the pivotal role of technological advancements. It scrutinizes the impact of social media, personalized marketing, and the burgeoning influence of streaming platforms on audience engagement and content distribution. The research further explores the prospective integration of artificial intelligence (AI), the proliferation of streaming platforms, and the potential of blockchain technology in revolutionizing film promotion and distribution. The conclusions drawn from this analysis underscore the significance of these technological shifts, offering insights into the future trajectories of the industry. This study provides a comprehensive understanding of the paradigmatic shift in marketing techniques, broadening the reach of film promotion to more realms and offering strategic implications for stakeholders.